Alternative Safety Box for Sharp Medical Waste in Health Screening of Disembarkation Pilgrims at Sukolilo Hajj Dormitory Surabaya: Case Report - Dani, Aprilia Mawar; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2024)
Hajj activities are mass gathering activities that produce medical waste and require special handling. Sharp medical waste from health service activity has a high potential to cause infection and injury. The disposal of sharp medical waste in mass gathering activities needed special attention. This case report occured during the disembarkation of pilgrims from SUB16 group from Madiun Regency, East Java on June 26, 2024 at the Sukolilo Hajj Dormitory, Surabaya. The use of mineral water bottle as an alternative safety boxes to accommodate sharp medical waste is reviewed based on the Regulations of the Minister of Health and FDA (Food and Drugs Administrations). The objective of this case report was to review whether mineral water bottle fulfill the criteria as alternative for safety box. Mineral water bottle cannot fulfill the criteria as alternative safety box for accommodating sharp medical waste. Alternative materials used as alternative safety box must have the characteristics of puncture-proof, having sufficient thickness, water-proof, easy to carry, and having striking colors.